Giao tiếp - Nguyễn, Quang (H. : ĐHQGHN, 2017)
This article focuses on the identification of “communication” viewed from different aspects with different emphases. Constituents, components, functions and types of communication... as seen by other researchers are brought to critical discussion. The author of the article introduces his own classification of communication and advances his own grouping of communication components.